2022
DOI: 10.1002/hsr2.472
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoalveolar lavage of ventilator‐associated pneumonia patients for antibiotic resistance and susceptibility test

Abstract: Background and Aims Ventilator‐associated pneumonia is highly prevalent nosocomial infection among patients under mechanical ventilation. Bronchoalveolar lavage (BAL) is effective in identifying the type of pathogen involved and determine the course of antibiotic. The aim of this study was to evaluate the prevalence of different pathogens involved in ventilator‐associated pneumonia (VAP) and associated antibiotic resistance and sensitivity pattern. Methods In this descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The most common pathogens reported for VAP were aerobic Gram-negative bacteria including P. aeruginosa, E. coli, K. pneumoniae and Acinetobacter, and Gram-positive bacteria such as S. aureus (15)(16)(17).…”
Section: Eric-pcr Results Of K Pneumoniaementioning
confidence: 99%
“…The most common pathogens reported for VAP were aerobic Gram-negative bacteria including P. aeruginosa, E. coli, K. pneumoniae and Acinetobacter, and Gram-positive bacteria such as S. aureus (15)(16)(17).…”
Section: Eric-pcr Results Of K Pneumoniaementioning
confidence: 99%
“…Similarly, 76.7% susceptibility of Klebsiella pneumoniae to meropenem in BAL specimens has been described in the recently published study (2022) conducted by Ahmadinejad et al . [ 9 ] The susceptibility profile of Acinetobacter spp. showed 83% intermediate results with colistin (similar to the study conducted by Ahmadinejad et al .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that 8% to 28% of mechanically ventilated patients develop Ventilator-associated pneumonia (VAP), which is 3 to 10 times more than patients who are not mechanically ventilated. Recent studies reported that several risk factors, such as trauma, duration of mechanical ventilation, sepsis, lung, and neurological disorders, acute respiratory distress syndrome, and previous use of antibiotics, increase the rate of VAP in patients [ 16 , 17 ]. Therefore, mechanical ventilation and its long duration should be avoided as much as possible, and patients with mechanical ventilation should continuously be screened for possible A. baumannii infection.…”
Section: Discussionmentioning
confidence: 99%